Students’ Perceptions on The Use of Local Accents in English Language Learning - Padmadevi, Putri Sekar; Wahyu, Rahmat; Khairunnisa, Asry (Journal of English Education, Literature and Linguistics, 2025)
This study aims to examine students' perceptions of the use of regional accents, especially the Surabaya (East Java) accent, in English language learning. This study involved 30 students, 6th semester English Education major, at Indraprasta PGRI University, with 15 selected responses analyzed in depth based on completeness and relevance. The study was conducted for one month using questionnaires and interviews, and triangulation was used to identify the data. With an emphasis on the case study of PuriViera, an Indonesian YouTuber living in the US, this study applied a qualitative descriptive method to analyze students' reactions to her YouTube Shorts and the perceptions that emerged. The findings of the study showed that most students expressed positive perceptions, recognizing the use of regional accents not as a deficiency but as an expression of identity that should be proud of, even introducing regional identities to a global audience. This study highlights the importance of inclusive pedagogical practices that support authentic communication and promote linguistic diversity.